Penguatan Pendidikan Akhlak Siswa Melalui Pembelajaran Kitab Adabul ‘Alim Wal Muta’allim Karya Syeikh Hasyim Asy’ari Di MAS Al Washliyah 12 Perbaungan - Iqbal Hafiz; Wahyudin Nur Nasution (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2025)
This article discusses the strengthening of students' moral education at MAS Al Washliyah 12 Perbaungan through learning the book of Adabul 'Alim wal Muta'allim. The discussion in this article focuses on the background of learning the book of Adabul 'Alim wal Muta'allim, the moral values contained in learning the book of Adabul 'Alim wal Muta'allim, the benefits and implementation of learning Adabul 'Alim wal Muta'allim which includes methods and evaluation in learning. The methodology used in writing this article is qualitative research with a case study approach. This research is located at MAS Al Washliyah 12 Perbaungan which is located at Jl. Malinda II, Batang Terap Village, Perbaungan District. The data collection techniques in this study were carried out by observation, interviews, and documentation. While the data analysis technique in the study used four stages, namely data collection, data reduction, data presentation, and conclusion drawing. The data validity technique carried out in this study uses creadibility techniques (credibility test) with source triangulation. The results of this study indicate that learning the book of Adabul 'Alim wal Muta'allim has a very positive impact on strengthening student morals. This is evident in the development of students' morals which are getting better during the learning of this book. The learning method used is the wetonan method. The choice of this method is because it is in accordance with the needs of students. The evaluation used in learning this book is formative, summative, and talaqqi evaluation